Effect of 12 Week Neuromuscular Weighted Rope Jump Training on Lower Extremity Reaction Time - Gökhan İpekoğlu; Ceren Suveren Erdogan; Fatmanur Er; Fatma Filiz Colakoglu; Gul Baltaci (Selcuk University, 2018)
The purposes of this study were to determine the inﬂuence of a jumping training protocol, using the weighted rope, on lower extremity visual and auditory reaction time performance in adolescent taekwondo (TKD) athletes. Twenty-two elite taekwondo athletes were randomly divided into two groups: the weigthed rope-trained (WRT) group (n = 11) and the control group (n = 11). Subjects in WRT group had jumping training 3 times a week for 12 weeks in addition to the routine taekwondo training program. The control group had no any training protocol in addition to the routine taekwondo training program. The visual and auditory reaction time performances of the subjects, both dominant and non-dominant legs were assessed with the Optojump System. The results of Paired Simple T test showed that the WRT decreased both the visual and the audiotory reaction time of non-dominant leg from pre to post-training (p=0,00, p=0,01 respectively). Although the pre-training audiotory and visual reaction times of dominant were similar between the groups (p gt;0,05), the post-training visual reaction time of dominant leg was significantly lower in the WRT group compared to control group (p=0,01). This study demonstrates that the weighted rope training program is effective in decreasing the reaction time in dominant and non-dominant leg. It is suggested that the WRT can be applied as an effective exercise program for enhancing visual and auditory reaction time performance.